Endorsement of â€œBlue Tickâ€ Celebgram: A New Phenomenon of Marketing Strategies Increasing Product Sales (Case Study on Instagram Account @avoskin) - Isrofi, Reni Mardiana (ARISTO, 2022)
Cosmetic has been a most wanted product nowadays, especially among teenage girls. In no time, local cosmetic enterprises have popped up. Most of these local cosmetic enterprises introduce and promote their products online through social media, especially Instagram. This research aims to find out Avoskin’s product marketing strategy that is done through endorsements to macro-influencers and to find out the impact of the endorsements on consumers’ decisions in purchasing the products. This research applies the qualitative descriptive method with a case study approach and collects data through interviews and observations. The result of this research shows that @avoskin only does endorsements to macro-influencers, in this case, are Instagram influencers with more than one hundred thousand followers, and are likely to have their accounts verified so-known as selebgram centang biru. In addition, from the results of interviews conducted via Instagram's Direct Message (DM) to 5(five) informants, it can be concluded that almost all informants know and decide to buy Avoskin products after seeing product reviews conducted by these selebgram centang biru, therefore the use of endorsements on the verified Instagram influencers has proven to be one of the consumers’ consideration to purchase the products, so the endorsement method used by Avoskin can continue to be used as a form of marketing strategy.